Scripture as communication: introducing biblical hermeneutics - Brown, Jeannine K. (Baker Academic, a division of Baker Publishing Group, 2021)
"This guide to the theory and practice of biblical hermeneutics emphasizes the communicative nature of Scripture, proposing a communication model as an effective approach to interpreting the Bible. Now revised and updated"--